A Reusable Approach to Network Service Orchestration - Lapacz, Roman; Filiposka, Sonja; Loui, Frederic; Szewczyk, Tomasz; Adamski, Marcin; Georgilakis, Konstantinos (My University, 2024)
The Network Infrastructure as Code paradigm empowers network engineers to create a repository of configuration templates and automation scripts, facilitating the automated configuration, management, and monitoring of the network infrastructure and services. Moreover, applying standardised approaches to high-level network processes, utilising a common data model for network description, and employing standardised open APIs for components, can offer reusability of the implementation of automated and orchestrated network solutions. In its recent activities, the GÉANT Global Platform for Labs (GP4L) group is actively collaborating with the Polish national research and education network (NREN) PIONIER focusing on developing a generalised, reusable approach to orchestrating service provisioning. By abstracting the process to define common steps in service provisioning, the goal is to provide a collaborative blueprint that other NRENs can adopt. The modular nature of the approach allows the creation of a repository of processes, subprocesses, and elementary tasks that can be reused across the community. This article presents the concept of developing generalised reusable processes and discuss challenges and decisions while working on the PIONIER use case. Aiming for reusability and sharing lessons learned, it builds towards a community of network automation and orchestration activities.
Keywords: Automation, orchestration, standardisation, workflows, service provisioning, network management